KEPEMIMPINAN TRANFORMASIONAL OLEH PEMIMPIN PENDIDIKAN (Suatu Kajian Membangun Paradigma Pemimpin Pendidikan) - Amin Haris (Jurnal Public Policy, 2015)
Education is defined as the effort to help students in gaining the maturity of thoughts which performed in a unit of organization, so that between one effort and the others are correlated to each other. Managing education by creating conducive and sustainable learning environment is a commitment in reaching agreement as an educational leader. Transformational leadership style used by the principals is very effective in developing schools become high achieving schools, through the efforts performed by the principals, such as: First,  in developing school vision and missions, the principals perform forgone observation and learn school culture, strengths and weaknesses at the beginning of their leadership at the schools, involve all school’s elements, socialize the target of school vision, and at last, the vision then formulated into measured missions as well as interpreted it in to clear school and communica-ted it to all school community.Key words: principal, transformational leadership, education